ANALYSIS OF YOUNG PEOPLE'S INTEREST IN RIVER AND SLUM TOURISM IN CI LIWUNG BIDARA CINA – MANGGARAI - Ulum, Miftahul; Handawati, Rayuna; Hijrawadi, Sony Nugratama (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2023)
River tourism is one of the river restoration efforts undertaken by several countries. Ci Liwung is the most polluted river in DKI Jakarta Province and is one of the dumping sites (water back landscape), in fact has tourism potential, namely river tourism and slum tourism. This study used a quantitative approach by distributing questionnaires and descriptive analysis. The results of the study show that young people have a low interest of 59.3%. Based on the indicators measuring interest, namely transactional interest, referential interest, and preferential interest, they are included in the low category, while explorative interest is included in the high category. Viewed based on the tourism component, inadequate tourist amenities both in terms of quality and quantity, different tourist attractions and accessibility, namely the distance between the location of residence and tourist sites is the cause of the low interest of young people in river tourism and slum tourism in Ci Liwung Bidara Cina – Manggarai. Keywords: Interests, Young People, River Tourism, Slums Tourism